Biogeografia de anuros neotropicais: filogeografia, padrões de distribuição e evolução de sinais acústicos - Guimarães, Felipe Camurugi Almeida (2018)
The distribution and diversification of species can be influenced by a variety of historical and ecological factors. Understanding these mechanisms is fundamental to deciphering how diversity is distributed at different scales, from taxa, lineages, phenotypes, and genealogies. The main goal of this thesis is to verify the importance of different historical and ecological processes in the distribution of neotropical anurans at different scales. In the first chapter, I used comparative approaches to investigate the influence of climatic niche overlap on the variability of the acoustic signals of a group of closely related species. Therefore, I used 15 anuran species from the Boana albopunctata group to test the following hypotheses: if related species are geographically overlapped, acoustic signals important for breeding and territoriality should be more different than expected by neutral evolution; alternatively, if calls present phylogenetic signal they must diverge in the climatic niche and geographic distribution, avoiding potential hybridization or interspecific competition. I generated a dated species tree and constructed niche models for most species. I analyzed 2088 calls of 212 individuals from 84 locations. Species tended to show low niche overlap, with divergence for most pairs of species. Advertisement calls had a strong phylogenetic signal. The results suggest that most of the diversification was allopatric with the maintenance of similar reproductive signals, supporting the second hypothesis. In the second chapter, I used Boana raniceps to test different diversification processes of the South American Diagonal of Open Formations (DOF) under a phylogeographic approach. I used multiple molecular markers, coalescent methods, ecological niche models, landscape genetics tools and acoustic signals to test: 1) whether there is only one lineage, widely distributed and genetically cohesive; 2) if the Central Brazilian Plateau uplift or landscape features in DOF influenced the species’ diversification; 3) whether climatic changes in the Quaternary influenced the demographic history of B. raniceps; 4) if potential genetic divergences were followed by differences in acoustic signals. I identified two lineages geographically structured: one from the Chaco, southwest of the Cerrado, and Amazonian savannas; another comprising the Caatinga and the northern/eastern portion of the Cerrado. The divergence between populations dated to the Mid-Pleistocene with high migration between them. Large areas of potential refuge were found for both lineages. The environmental niche differentiated between lineages, as well as the advertisement calls. Boana raniceps occur in lowlands and it is possible that the uplift of the Central Plateau, along with a climatic filter, has historically acted as a semipermeable barrier, reducing the gene flow between both populations. These results reinforce the complex scenario of biodiversity diversification and distribution in the world’s most biodiverse region.